Corrosion behavior of biodegradable Mg-based alloys via femtosecond laser surface melting - Park, Jaeho; Han, Hyung-Seop; Park, Jimin; Seo, Hyunseon; Edwards, James; Kim, Yu-Chan; Ok, Myoung-Ryul; Seok, Hyun-Kwang; Jeon, Hojeong (Elsevier BV, 2018)
The effects of femtosecond (fs) laser treatment on a biocompatible Mg-Ca-Zn alloy were systemically analyzed. The fs laser altered the surface microstructure of the Mg-Ca-Zn alloy, resulting in reduced corrosion through localized melting and rapid solidification. Treatment with appropriate laser energy (500 Hz) generated an exceptionally thin modified layer (similar to 2 mu m) with a uniformly refined microstructure. Laser-induced remelting of the secondary phase reduced galvanic corrosion and prevented the occurrence of pitting corrosion, resulting in overall reduced corrosion. Results reveal that the corrosive nature of the biodegradable Mg alloy can be controlled through surface modification by a fs laser. (C) 2018 Elsevier B.V. All rights reserved.